1987
DOI: 10.1159/000174203
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Oxygen Consumption during Exercise Testing in Peripheral Vascular Disease

Abstract: Exercise testing on a treadmill was performed in 15 patients with peripheral vascular disease to determine the pattern of oxygen consumption during exercise. A plateau in the oxygen consumption over the final 90 s of exercise was used as a criterion for maximal effort and only 4 out of 15 (27%) obtained a plateau of oxygen consumption compared to 20 out of 26 (77%) normal subjects (χ2 7.9, p < 0.005). These findings may account for the limited value of exercise testing in detecting coronary artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
4
3
0
Order By: Relevance
“…Exercise tolerance and ability to walk on level ground are severely reduced among individuals with symptomatic lower extremity arterial disease." 24,25 The current study extends these findings to individuals with mild asymptomatic disease. Occlusive atherosclerotic lesions in the major arteries of the leg limit blood flow to the muscle and cause ischemic pain during exercise.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Exercise tolerance and ability to walk on level ground are severely reduced among individuals with symptomatic lower extremity arterial disease." 24,25 The current study extends these findings to individuals with mild asymptomatic disease. Occlusive atherosclerotic lesions in the major arteries of the leg limit blood flow to the muscle and cause ischemic pain during exercise.…”
Section: Discussionsupporting
confidence: 69%
“…Exercise tolerance and ability to walk on level ground are severely reduced among individuals with symptomatic lower extremity arterial disease 6,24,25 . The current study extends these findings to individuals with mild asymptomatic disease.…”
Section: Discussionsupporting
confidence: 63%
“…, 1990) in PAD patients, typically half that of age‐matched controls. The results of the present study also agree with previous studies which have demonstrated a large degree of heterogeneity in physiological responses to graded exercise test in PAD patients (Eldridge & Hossack, 1987; Ryan et al. , 2000).…”
Section: Discussionsupporting
confidence: 93%
“…The data from the graded exercise test are in agreement with previous studies demonstrating severely attenuated oxygen uptake (Hiatt et al, 1990) in PAD patients, typically half that of age-matched controls. The results of the present study also agree with previous studies which have demonstrated a large degree of heterogeneity in physiological responses to graded exercise test in PAD patients (Eldridge & Hossack, 1987;Ryan et al, 2000). Maximum walking time and levels of oxygen consumption were similar in the present study to those previously reported (Gardner et al, 1991;Womack et al, 1997;Labs et al, 1999b;Ryan et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…(11) This may be a consequence of an altered gait pattern observed even before the development of claudication pain,(1214) but this is not a consistent finding. (1517) When the impaired walking economy (i.e., high oxygen uptake) of patients with intermittent claudication is considered along with their low peak oxygen uptake,(1820) pain-free ambulation at any given pace is performed at a higher relative metabolic cost than compared to controls. (11) The onset of claudication may impair walking economy even further, thereby increasing the relative metabolic cost of painful ambulation and reducing exercise tolerance of patients with intermittent claudication.…”
Section: Introductionmentioning
confidence: 99%